2013
DOI: 10.5114/reum.2013.38386
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rheumatoid arthritis on the economic situation of Polish households

Abstract: <b>Cel pracy: </b>Reumatoidalne zapalenie stawów (RZS), jako choroba przewlekła, stopniowo ograniczająca sprawność chorego, wpływa na kondycję ekonomiczną jego gospodarstwa domowego. Schorzenie to z jednej strony wymaga ponoszenia kosztów na leczenie i dostosowanie środowiska chorego, z drugiej natomiast ogranicza możliwości zarobkowe jego i jego rodziny. Celem pracy było oszacowanie kosztów RZS oraz wykazanie, czy choroba wpływa na kondycję ekonomiczną gospodarstwa domowego chorego.<br /> &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The results of a study carried out in the years 2009–2010 in Poland, which included 1000 respondents suffering from RA (average age of 60 years) who were the patients of 50 rheumatology out-patient clinics selected at random, showed that 53% of RA patients received legal disability status. Among them 35% (19% of all respondents) are considered to be severely disabled while 64% (33% of all respondents) have a moderate degree of disability [ 20 ]. As many as 41% of respondents stated that they needed to adapt their living conditions to the limitations resulting from the disease, and only 5% out of 1000 respondents stated that they had already adjusted their environment.…”
Section: Disabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a study carried out in the years 2009–2010 in Poland, which included 1000 respondents suffering from RA (average age of 60 years) who were the patients of 50 rheumatology out-patient clinics selected at random, showed that 53% of RA patients received legal disability status. Among them 35% (19% of all respondents) are considered to be severely disabled while 64% (33% of all respondents) have a moderate degree of disability [ 20 ]. As many as 41% of respondents stated that they needed to adapt their living conditions to the limitations resulting from the disease, and only 5% out of 1000 respondents stated that they had already adjusted their environment.…”
Section: Disabilitymentioning
confidence: 99%
“…As many as 41% of respondents stated that they needed to adapt their living conditions to the limitations resulting from the disease, and only 5% out of 1000 respondents stated that they had already adjusted their environment. The most frequent adaptations include appropriate bathroom equipment (6%) and purchase of a dishwasher (5%) [ 20 ].…”
Section: Disabilitymentioning
confidence: 99%
“…As many as 49% of RA patients’ households experience financial difficulties, with 20% of households reporting financial difficulties in the Central Statistical Office studies. The assistance of third parties considerably influences the costs of RA [ 16 ].…”
Section: Indirect Costs Of Rheumatoid Arthritis In Polandmentioning
confidence: 99%
“…Rheumatic diseases result in: progressive loss of productivity [ 8 ], increasing difficulties in performing everyday activities [ 9 ], often ending finally in total dependency on others [ 10 ]. The above-mentioned dynamics results in limited ability of patients with rheumatic diseases to gain income and, at the same time, in doubling of health-related expenses [ 11 ]. In old age, apart from rheumatoid arthritis, typically mentioned in this context, the most common rheumatic diseases sensu lato include: systemic involvement of connective tissue and gout [ 12 ].…”
Section: Introductionmentioning
confidence: 99%